Cyber security of critical infrastructures - Maglaras, Leandros A. (2018)
Modern Supervisory Control and Data Acquisition (SCADA) systems are essential for monitoring and managing electric power generation, transmission and distribution. In the age of the Internet of Things, SCADA has evolved into big, complex and distributed systems that are prone to be conventional in addition to new threats. Many security methods can be applied to such systems, having in mind that both high efficiency, real time intrusion identification and low overhead are required.